2019
DOI: 10.1038/s41467-019-13343-7
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and receptor-interacting residues of MYDGF — a protein mediating ischemic tissue repair

Abstract: Myeloid-derived growth factor (MYDGF) is a paracrine-acting protein that is produced by bone marrow-derived monocytes and macrophages to protect and repair the heart after myocardial infarction (MI). This effect can be used for the development of protein-based therapies for ischemic tissue repair, also beyond the sole application in heart tissue. Here, we report the X-ray structure of MYDGF and identify its functionally relevant receptor binding epitope. MYDGF consists of a 10-stranded β-sandwich with a foldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The 80 residues of human MYDGF that were identical to zebrafish MYDGF in the sequence alignment (58% sequence identity) were mapped onto the NMR solution structure of human MYDGF. The structure presented herein was solved using NMR data ( Bortnov et al, 2019 ) to obtain a refined solution structure of human MYDGF that has been subsequently reconciled with the crystal structure ( Ebenhoch et al, 2019 ) as described in ( Bortnov, 2020 ) and deposited under PDB accession no. 6O6W .…”
Section: Methodsmentioning
confidence: 99%
“…The 80 residues of human MYDGF that were identical to zebrafish MYDGF in the sequence alignment (58% sequence identity) were mapped onto the NMR solution structure of human MYDGF. The structure presented herein was solved using NMR data ( Bortnov et al, 2019 ) to obtain a refined solution structure of human MYDGF that has been subsequently reconciled with the crystal structure ( Ebenhoch et al, 2019 ) as described in ( Bortnov, 2020 ) and deposited under PDB accession no. 6O6W .…”
Section: Methodsmentioning
confidence: 99%
“…The other chain was identified as L1 and the register assignment was validated by the presence of the disulfide bond between C147 and C169 (see Figure S5E). The Fab domains were built from templates created by docking the individual Ig domains from the heavy chain of PDB: 6SVL (Ebenhoch et al, 2019) and the light chain of PDB: 5E94 (Hennen et al, 2016) into the density. The full L1-L7/4G10 Fab model was built in Coot and subjected to rounds of iterative real-space refinement in Phenix (Liebschner et al, 2019) followed by manual corrections in Coot and ISOLDE (Croll, 2018).…”
Section: Luminal Domainmentioning
confidence: 99%
“…The N-terminus and C-terminus of human C19orf10 contain a signal peptide and a conserved sequence of the endoplasmic reticulum, respectively, but human C19orf10 has no sequence homology with any other proteins [9]. Structural analysis has revealed that C19orf10 consists of 10 antiparallel β-strands forming a β-sandwich, and its folding topology is not similar to other cytokines or growth factors [10]. Furthermore, functional studies have demonstrated that C19orf10 promotes angiogenesis [11,12], inhibits myocardial cell apoptosis, promotes vascular endothelial cell proliferation, and plays a role in cardiac repair [7,13].…”
Section: Introductionmentioning
confidence: 99%